ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BELANJA DAERAH KABUPATEN/KOTA DI PROVINSI KEPULAUAN BANGKA BELITUNG - Laila Mulia Dayanti (2023)
Regional spending is an important part of the economy of a regional government for the welfare of its people through spending with the right realization in creating public services in building facilities and infrastructure so that it can be enjoyed and utilized properly by all levels of society. Regional spending spent by the government is influenced by various factors. The purpose of conducting this research is to find out and analyze what factors can influence regional spending in the districts/cities of the Bangka Belitung Islands Province in 2013-2020. The population in this study is the districts/cities of the Bangka Belitung Islands Province. The sample used in the findings of this study was from 2013-2020 for eight years and there were 56 data observers from the Central Bureau of Statistics. The research method used is Fixed Effect panel data assisted by Stata 12 software. The independent variables used in this finding are total population, regional original income, gross regional domestic product, and income inequality. As for the trick variable, namely regional spending in the districts/cities of the Bangka Belitung Islands Province in 2013-2020. From the results of estimation and statistical processing, it was found that the total population, original regional income, gross regional domestic product and income inequality of the Bangka Belitung Islands Province significantly positively affected regional expenditures, while the gross regional domestic product of the Bangka Belitung Islands Province did not significantly affect regional expenditures.